Implications of fluorodeoxyglucose uptake in low-intermediate grade metastatic neuroendocrine tumors from peptide receptor radionuclide therapy outcome viewpoint: A semi-quantitative standardized uptake value-based analysis - Adnan, Aadil; Sampathirao, Nikita; Basu, Sandip (World Journal of Nuclear Medicine, 2019)
Dual tracer positron emission tomography (PET) imaging approach (with 68Ga-DOTATATE PET-computed tomography (CT) for somatostatin receptor and 18-fluorodeoxyglucose (18FDG) PET-CT for glucose transporter receptor) plays a vital role in baseline differentiation, treatment decision-making, and prognostic assessment of neuroendocrine tumors (NETs). The aims of this study were to observe and compare the clinical behavior of low-/intermediate-grade NETs depending on their baseline FDG metabolism (calculated through pre-peptide receptor radionuclide therapy [PRRT] FDG standardized uptake value [SUV]) and to determine its prognostic importance in predicting extent of therapeutic response (post-PRRT) in terms of symptomatic, biochemical, and scan parameters along with the long-term impact on progression-free survival (PFS) and overall survival (OS). Fifty-nine patients with low (≤2%) and intermediate (3–20% Mib-1/Ki-67 index) grade metastatic NET were selected for this retrospective analysis and divided into three groups: Group 1 consisted of patients having low-grade FDG uptake at baseline, predefined as SUVmax< 5 (n = 13); Group 2 consisted of those having intermediate-grade FDG uptake at baseline, SUVmax5–10 (n = 34), and Group 3 consisted of patients having high-grade FDG uptake at baseline, defined as SUVmax>10 (n = 12). The trend of FDG avidity was studied from the baseline till the time of analysis and the overall outcomes were compared in terms of symptomatic response (Karnofsky and ECOG performance score), biochemical response, scan response (anatomical and metabolic, RECIST 1.1 and PERCIST 1.0), PFS and OS. Patients in Groups 1 and 2 showed highest proportion of symptomatic complete response, biochemical partial response, and stable disease on scan. These patients also demonstrated better PFS and OS and lowest hazard ratio compared to patients in the Group 3. An important finding was a substantial fraction of the complete metabolic responders (CMRs) across the groups, achieved CMR within first 2 cycles of PRRT (85% of Group 1, 51% of Group 2, and 47% of Group 3). In conclusion, most of the patients of low-/intermediate-grade NET having low-to-moderate baseline tumor FDG metabolism (SUVmax≤10) showed favorable symptomatic response with good biochemical and anatomical disease control and were associated with prolonged PFS and OS, compared to that of those having high-grade baseline tumor FDG metabolism (SUVmax> 10).
Keywords: 177Lu-DOTATATE; fluorodeoxyglucose-positron emission tomography/computed tomography; neuroendocrine tumor; peptide receptor radionuclide therapy; survival; treatment response; tumor grade